Investigation of Emerging Risk Factors and Isolation of Potential Pathogenic Bacteria from Domestic Dog Stool in Port Harcourt Metropolis, Niger Delta - O Azuonwu; B Kemsi; R.F Njoku-Tony; Wokem G.N. (Journal of Zoological Research, 2020)
This study investigated the potential pathogenic bacteria that are associated with domestic dog stool in Port Harcourt Metropolis. Convenience sampling techniques were used for sample collection outcome. A total of fifty dog stool samples were collected aseptically into a sterile stool container from different locations (Agip Estate, Rumuokoro Community, Government Residential Area, Sand-fill Borokiri, Port Harcourt Township, and Rivers State University lecturers’ quarters) all within Port Harcourt City. Bacteriological analysis was determined using standard microbiological analytical and identification techniques. Statistical analysis was performed using Statistical Package for Social Science version 21 for frequency, percentage, prevalence rate and correlation at 0.01 and 0.05 level of significance. Potential pathogens with associated percentages that were isolated are E coli (20.0%), Klebsiella species (16.0%), Pseudomonas species (4.0%), Proteus species (28.0%), Bacillus species (4.0%), Staphylococcus aureus (14.0%), and unidentified [other Staphylococcus species] (4.0%). However, the research further revealed that Proteus species (28.0%), was the most prevalent pathogen, while Bacillus species (4.0%), Pseudomonas species (4.0%), and Streptococcus species (4.0%), were the least prevalent among pet dogs studied. The correlation analysis showed no significant relationship between isolates with socio-demographic data of pet owner and Pet biodata respectively. From the analysis, correlation coefficient values of .269 and .124 were obtained for Age of Pet Owner and Gender of Owner respectively. It also show a direct correlation but by implication, a very weak, non-significant (p<0.05) relationship existed between the organisms isolated and the variables (Age of Pet Owner and Gender of Pet Owner). However, no relationship exists between isolates and visit to vet Doctor (r-0.038; p>0.05). Furthermore, negative non-significant correlation (p>0.05) was observed for marital status of Pet Owner (r=-.158) and Age of Pet (r=-.023) and isolate. Also, correlation association between isolates and some risk factors using the correlation analysis matrix revealed an indication of an indirect but moderate association between isolates and Caressing (r=-.347, p=0.01). However, other risk factors like vaccination (r=.042), Feeding Pattern(r=.125), Pet Bathing (r=.220) and Eating with pet in same plate (r=.146), did not prove statistical significance at p>0.05. The results from the study strongly suggest that pet dogs carry potential pathogenic organisms in their faecal matter that can serve as a source of infection to the pet owners. It is, therefore, very critical that these pets should be treated and possibly vaccinated frequently, even as their faecal matters should be well disposed to prevent possible zoonotic infectious epidemic outbreak in our global communities.
Keywords: Zoonotic infection